Pencegahan dan Penanganan Kekerasan Seksual Bagi Mahasiswa di Lingkungan Perguruan Tinggi Provinsi Sumatera Selatan: Sosialisasi Permendikbud Ristekdikti No. 20 Tahun 2021 - Yusni Arni; Maharani Putri, Dian (PELITA NUSA TENGGARA, 2024)
Higher education is synonymous with campus life, as one of the educational institutions that is the heart of civilization and produces educated citizens. Universities are one of the educational institutions most vulnerable to sexual violence. Sexual harassment at universities has a negative impact on education in Indonesia. So far, most allegations of sexual harassment have ended peacefully; However, there are several reports that have been processed for months and have not yet produced clarity. There needs to be socialization of regulations that can be implemented to increase students' knowledge about sexual violence. Sexual harassment at universities has a negative impact on education in Indonesia. So far, most allegations of sexual harassment have ended peacefully; However, there are several reports that have been processed for months and have not yet produced clarity. There needs to be socialization of regulations that can be implemented to increase students' knowledge about sexual violence. Sexual harassment at universities has a negative impact on education in Indonesia. So far, most allegations of sexual harassment have ended peacefully; However, there are several reports that have been processed for months and have not yet produced clarity. There needs to be socialization of regulations that can be implemented to increase students' knowledge about sexual violence. The presence of PERMENDIKBUDRISTEK No. Law No. 30 of 2021 concerning Prevention and Handling of Sexual Violence and Law No. 30 of 2022 concerning sexual violence should be used as a means and legal umbrella for survivors/victims and all parties. involved. This legislation is a step forward, allowing higher education providers to take decisive action in response to each report. Based on the results of the evaluation of service activities carried out by the service team from the Faculty of Economics, Sriwijaya University, there was an increase in understanding and knowledge about the prevention and treatment of sexual violence at universities in Palembang City. The target is 37 students and university students with an average knowledge level of 86.2 percent. Perguruan tinggi identik dengan kehidupan kampus, sebagai salah satu lembaga pendidikan yang menjadi jantung peradaban dan mencetak warga negara yang terdidik. Perguruan tinggi merupakan salah satu lembaga pendidikan yang paling rawan terhadap kekerasan seksual. Pelecehan seksual di universitas memberikan dampak negatif terhadap pendidikan di Indonesia. Sejauh ini, banyak tuduhan pelecehan seksual yang berakhir dengan damai; Namun, ada beberapa laporan yang sudah diproses berbulan-bulan dan belum membuahkan kejelasan. Perlu ada sosialisasi peraturan yang dapat diterapkan untuk meningkatkan pengetahuan siswa tentang kekerasan seksual. Pelecehan seksual di universitas memberikan dampak negatif terhadap pendidikan di Indonesia. Sejauh ini, banyak tuduhan pelecehan seksual yang berakhir dengan damai; Namun, ada beberapa laporan yang sudah diproses berbulan-bulan dan belum membuahkan kejelasan. Perlu ada sosialisasi peraturan yang dapat diterapkan untuk meningkatkan pengetahuan siswa tentang kekerasan seksual. Kehadiran PERMENDIKBUDRISTEK No UU No 30 Tahun 2021 tentang Pencegahan dan Penanganan Kekerasan Seksual serta UU No 30 Tahun 2022 tentang kekerasan seksual hendaknya dapat dijadikan sarana dan payung hukum bagi penyintas/korban dan semua pihak. terlibat. Undang-undang ini merupakan sebuah langkah maju, yang memungkinkan penyelenggara pendidikan tinggi mengambil tindakan tegas dalam menanggapi setiap laporan. Berdasarkan hasil evaluasi kegiatan pengabdian yang dilakukan oleh tim pengabdian Fakultas Ekonomi Universitas Sriwijaya, terjadi peningkatan pemahaman dan pengetahuan tentang pencegahan dan pengobatan kekerasan seksual pada perguruan tinggi di Kota Palembang. Sasarannya terdiri dari pelajar dan mahasiswa sebanyak 37 orang, dengan rata-rata tingkat pengetahuan sebesar 86,2 persen.